2016
DOI: 10.1039/c5tc03352g
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism-dependent aggregation induced emission of a push–pull dye and its multi-stimuli responsive behavior

Abstract: A push–pull dye with AIE polymorphism-dependent properties shows mechano-, thermo- and chrono-chromism associated with stimuli-induced surface structural defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 96 publications
2
41
0
Order By: Relevance
“…Crystal structures of the series 1, 10a and compounds 2b 12 and 5a 13 were previously reported by us, together with a thorough discussion, supported with DFT and TDDFT calculations, [11][12][13] of the structure-optical property relationships governing their emissive behaviour. It was found that their AIE properties were strictly related to their crystal structure, which is able to activate a RIR process.…”
Section: X-ray Crystal Structuressupporting
confidence: 59%
See 2 more Smart Citations
“…Crystal structures of the series 1, 10a and compounds 2b 12 and 5a 13 were previously reported by us, together with a thorough discussion, supported with DFT and TDDFT calculations, [11][12][13] of the structure-optical property relationships governing their emissive behaviour. It was found that their AIE properties were strictly related to their crystal structure, which is able to activate a RIR process.…”
Section: X-ray Crystal Structuressupporting
confidence: 59%
“…All the compounds reported in Table 1 show a very low PL QY in solution, which does not depend much on the polarity of the solvent. Compounds 1a, 10a 2b, 12 2e, 3a, 3b and 5a 13 show solvatochromic behaviour related to their push-pull molecular structure (see ESI †) without any relevant variation in emission intensity.…”
Section: Molecular Optical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered that, connecting the groups of hydrogen bonding factor,e .g.,o xygen-containing or nitrogen-containing groups,t ot he two sides of fluorene may achievet he same effect as fluorenone for the construction of stimuli-responsive SLS molecules.T his approach for the design of functional molecules may likewise result in metastables olid/ crystalline structures because of the competition between p-p stacking and hydrogen bonding, which is ap rerequisite of the reversible phase transformationso fs timuli-responsive SLS molecules. [42][43][44][45][46][47][48][49][50] In this paper,w er eported as mall organic molecule, 4,4'-(9,9-dimethyl-9H-fluorene-2,7-diyl)dipyridine (MFDP, Scheme 1), which exhibited three different crystal polymorphs with different luminescentc olor.M oreover,a ll three polymorphsd isplayh igh solid luminescente fficiency and showed an ovel tricolor fluorescent switching from violet to blue and to green upon heating or grinding. The single crystalso ft he three crystal polymorphs were obtained, and their phase transformation and photophysical properties were comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to aggregation-caused quenching (ACQ) of traditional fluorophore, TPE derivatives can exhibit strong emission when they are aggregated or in the solid state [29,30,31]. At the same time, tetra-phenyl ethylene (TPE) is a typical fluorophore which processes the advantages of facile synthesis and easy structural modification; numerous functional groups can be attached to it through simple reactions, so it was chosen as the AIE fluorescence core in this study.…”
Section: Resultsmentioning
confidence: 99%